The Intra-nuclear SphK2-S1P Axis Facilitates M1-to-M2 Shift of Microglia via Suppressing HDAC1-Mediated KLF4 Deacetylation - Ji, Juan; Wang, Juan; Yang, Jin; Wang, Xi-Peng; Huang, Jing-Jing; Xue, Teng-Fei; Sun, Xiu-Lan (Frontiers in Immunology, 2019)
Sphingosine 1-phosphate (S1P) regulates a variety of cellular responses including microglial activation and polarization. However, the impacts of S1P on ischemia-induced microglial activation and polarization remain unclear. In the present study, Sprague-Dawley rats were subjected to middle cerebral artery occlusion (MCAO) and treated with S1P analogue FTY720 (0.5, 1, 2 mg/kg) for 24 h. The impacts of FTY720 on oxygen-glucose deprivation (OGD)-induced microglial polarization were examined in the primary cultured microglia. FTY720 treatment could prevent ischemia-induced brain injury and neurological dysfunction, also decrease the levels of IL-1β and TNF-α and promote M2 microglial polarization in rats. Further, we found that FTY720 inhibited the expressions of M1 markers, but increased the expressions of M2 markers in the OGD-insulted microglia. And FTY720 could enhance the phagocytic function of microglia. The sphingosine kinase 1/2 (SphK1/2) or the Sphk2 inhibitor could prevent the M1 to M2 phenotype shift improved by FTY720, but the Sphk1 inhibitor failed to affect the roles of FTY720. Furthermore, the Sphk1/2 or Sphk2 inhibitor promoted the activities of histone deacetylase (HDAC1) and inhibited the histone acetylation of the Krüppel-like factor 4 (KLF4) promoter regions, indicating that intra-nuclear pFTY720 inhibited HDAC1 activations and prevented KLF4 to interact with HDAC1, and thereby suppresses KLF4 deacetylation. Therefore, our data reveals that intra-nuclear SphK2-S1P axis might facilitate the switch of microglial polarization from the M1 phenotype to the M2 phenotype, which might be intra-nuclear regulatory mechanisms of FTY720-prevented neuroinflammation.